What do youth need to know about puberty? A scoping review protocol to identify puberty education competencies - Marie A. Brault; Nanki Singh; Nikita Kakkad; Melissa Peskin; Anthony Betori; Gregory Laynor; Emily Naiser (PLoS ONE, 2026)
Introduction Puberty is a key transition point in adolescents’ lives that plays a foundational role in shaping health behaviors and outcomes across one’s life course. This period holds significant potential to empower adolescents and support autonomy in health and well-being, but limited puberty education curricula exist for early adolescents (age 8–14), and those that do exist vary in content. There is a paucity of evaluations of puberty competencies and limited consensus on what competencies should be measured to assess effectiveness or even how to measure these competencies. Objective The objective of this scoping review is to systematically map and characterize the outcomes, domains, and instruments used to evaluate puberty education curricula for early adolescents aged 8–14 years. In accordance with PRISMA-ScR and JBI scoping review guidance, this review does not synthesize effect sizes or assess intervention efficacy, but maps the breadth of evidence to identify conceptual gaps and inform future framework development. Methods The review protocol is registered with the Open Science Framework (OSF). We will search PubMed, CINAHL, PsycInfo, ERIC, Education Source, Scopus, Web of Science Core Collection, ProQuest Dissertations and Theses Global, and OpenAlex for relevant sources. Two reviewers will independently screen and extract studies that meet inclusion criteria using our data extraction tool. Expected outputs Findings from the scoping review will be synthesized to create an overarching framework that can guide approaches to the development and evaluation of puberty curricula targeted to early adolescents. Focus group discussions with adolescents, parents, and school representatives will be conducted to assess the applicability and appropriateness of identified competencies and evaluation measures prior to broader dissemination. Insights from this scoping review will ultimately be used to inform the implementation and evaluation of puberty education.